The Criterion of Significance of Violations of Material and Procedural Law in the Exercise of Cassation Appeal in Civil Proceedings - Taras A. Bondarenko (Сибирское юридическое обозрение, 2017)
This article is devoted to the problem of fixing in the chapter of the Code of Civil Procedure of the Russian Federation, regulating the procedure in court of the cassation instance, a single criterion of significant violations of material and procedural law standards, as well as determining the content of “guidelines” for both the applicant and the court, providing for the unconditional cancellation of judicial decisions of lower courts. The Author comes to the conclusion that the presence in the Civil Procedure of the Russian Federation of such stable phrases as “significant violations of the norms of substantive and procedural law” and the absence of their normative interpretation significantly limit the exercise of the right of citizens to access to court.